ANALYSIS OF THE EFFECT OF CASH ON DELIVERY PAYMENT METHODS ON CONSUMER PURCHASE DECISIONS ON THE TIKTOK SHOP PLATFORM - Endarwati, Esti Tri; Desfitrina, Desfitrina (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
This study aimed to analyze the effect of the cash-on-delivery payment method on consumer purchasing decisions on the Tiktok Shop platform. This research uses quantitative research. The types of data used in this research are primary and secondary data. The variables in this study are divided into two, namely the independent variable and the dependent variable. The independent variable (X) is the COD method, while the dependent variable (Y) is the consumer purchasing decision. Primary data were obtained from questionnaires distributed to 30 research respondents. At the same time, secondary data was obtained from previous research literature studies. Analysis of research data using validity test, reliability test, simple regression test and hypothesis testing (partial test), and analysis of the coefficient of determination. Based on the data analysis and discussion results, it can be concluded that the Cash on Delivery payment method has a positive and significant effect on Consumer Purchase Decisions on the TikTok platform. This is because the lifestyle of the people in the city of Palembang has turned into a wasteful society, including the respondents generally like something easy and practical so that it will lead to satisfaction in purchasing decisions.